Personality as a Determinant of Customer Experience Quality and Value-in-Use in a Public Crisis Situation – The Case of E-Learning - Katharina Lohmann (Junior Management Science (JUMS), 2022)
This thesis was designed to investigate whether differences exist between students' personalities regarding their perceived Customer Experience Quality and their perceived Value-in-Use, for the case of e-learning. In particular, the personality dimension Introversion-Extraversion was investigated. Furthermore, it was examined whether students' Fear of the Coronavirus Disease 2019 moderates the relationship between Introversion-Extraversion and the perceived Customer Experience Quality as well as the relationship between Introversion-Extraversion and the perceived Value-in-Use. Using survey data on asynchronous e-learning as well as survey data on synchronous e-learning, multiple two-way ANOVAs were conducted. It was found that no significant differences for either asynchronous e-learning or synchronous e-learning regarding the Customer Experience Quality and the Value-in-Use exist between introverted and extraverted students. Furthermore, no significant interaction effect on the perceived Customer Experience Quality and Value-in-Use was found for introverted and extraverted students with either low or high Fear of the Coronavirus Disease 2019.
Keywords: 650; COVID-19; e-learning; introversion-extraversion; customer experience quality; value-in-use; two-way ANOVA